Protocol of the mat Pilates Method in elderly (Research, Society and Development, 2022)
Objective: To develop and test a Pilate’s mat protocol, without accessories, in the elderly and to describe their perceptions. Methodology: In this qualitative and survey study, 11 elderly participated with a mean age of 69.7 (SD=6.69). The elderly underwent a three-week intervention, twice a week, lasting 60 minutes each session, with the practice of the Pilates mat protocol without accessories. Results: The students obtained 88.3% of attendance in the sessions. Observations were made in the first and last intervention sessions regarding the perception of the elderly in relation to the difficulty and execution of the exercises (with little difficulty being reported by the elderly), the breathing technique (classified as good) and coordination with the exercises (indicated as regular in the first session and as good in the last), the activation of the core (both in the first and in the last session its activation was good) and the verbal and tactile stimuli from the teacher (considered as good) and the visual ones (as very good). Conclusion: The elderly were satisfied with the protocol developed, exercises, breathing, core activation and teacher stimuli.